The Perceptions of English Education Students Towards the Use of Code-mixing in English and Teaching Learning Process at UIN Sayyid Ali Rahmatullah Tulungagung - Zubaedah, Zubaedah; Chojimah, Nurul (Journal of English for Academic and Specific Purposes (JEASP), 2023)
This study aims to find out the perceptions of English education students in the sixth semester toward the use of code-mixing in the main activity of the teaching and learning process at UIN Sayyid Ali Rahmatullah Tulungagung. The research design is a survey with a quantitative approach. The data were obtained from 26 English students in the sixth semester that had filled out a link questionnaire that had been distributed. Based on findings obtained from the questionnaire, revealed that 77% of students have a positive perception, they also agreed that the use of code-mixing has a positive impact on them; it can be used to make fun and lively learning in the classroom and easy to understand the lesson. 19% of students have a neutral perception of the impact of code-mixing. Then, 4% of students who have a negative perception think that code-mixing does not positively impact them, and they feel uncomfortable when using code-mixing in the English teaching and learning process.